Interoperabilidade BIM e BEM: avaliação de eficiência do sistema na análise energética de edifícios - Pretti, Argeu Leonidas Maioli (2018)
The growing energy demand imposes a paradigm shift with regard to issues of generating sources and the means to make their use more sustainable. The construction industry plays an important role, considering that the energy consumption of the sector is very significant throughout the life cycle of a building, however, a series of tools have arisen with the purpose of making the Architecture, Engineering and Construction - AEC more efficient and with less environmental impact, being Building Information Modeling (BIM) and the Building Energy Modeling (BEM) programs that are part of this group. The research seeks to evaluate the interoperability performance between the BIM and BEM tools after the sharing of the Reference and Adjusted models, and their parameters calculated by the RTQ-C Prescriptive Method. The models created from the standard building had their wrappers detailed in the BIM Autodesk® Revit® tool and shared with the BEM tools - Green Building Studio; EnergyPlus; eQUEST; DesignBuilder; IES-VE; OpenStudio and Insight through the two standard formats of interoperability, IFC and gbXML, and the derivatives of gbXML - IDF and INP. Three tools did not perform simulations after interoperability, either importing gbXML and IFC files or loading the IDF and INP files. Among the tools that performed the simulations, only EnergyPlus presented coherent and consistent results after loading the IDB files derived from gbXML from the Green Building Studio tool and the Insight plugin.